Subwersja dziewictwa w filozofii Luce Irigaray - Araszkiewicz, Agata (Śląskie Studia Polonistyczne, 2019)
Symbolically subversive facet of the virginity motif in Luce Irigaray’s philosophy is the major focus of the presented text. It commences by citing a thesis by Claude Lévi-Strauss speaking of the patriarchal social structure, which exercises heteronormative sexuality and reproduction control, being based upon the principle of the exchange of women. What the said subjugation of women and turning them into means of exchange by masculine subjects entails, is repression of feminine subjectivity, corporeality, sexuality, masculine dominance becoming paramount, and the coercion of heterosexual male substitution, that is, transformation of women into replaceable entities. Irigaray calls this phenomenon “the women market” – the principle of patriarchal culture which establishes their prices based on their structural position in circulation. The virgin – an obvious sign of transaction taking place between men – is utilized by Irigaray as a basis for a new project of female autonomy which, in turn, instigates entirely new order of the corporeal, drives and desires, designed for symmetricity closeness, and relationality. Juxtaposing this project with a category of “self-excitability,” which sees feminine subjectivity as immanently causative, lead us to a redefinition of the traditional pattern of sexuate/sexual difference founded on hierarchy and repression, aimed at the ethics of sexual/sexuate difference and their inclusive openness to newly-defined, variegated, and manifold subjectivities.